2017
DOI: 10.1103/physreva.95.063840
|View full text |Cite
|
Sign up to set email alerts
|

Intensified antibunching via feedback-induced quantum interference

Abstract: We numerically show that time delayed coherent feedback controls the statistical output characteristics of driven quantum emitters. Quantum feedback allows to enhance or suppress a wide range of classical and nonclassical features of the emitted quantum light. As exemplary quantum system, we use a pumped cavity containing two emitters. By applying phase-selective feedback, we demonstrate that photon antibunching and bunching can be increased in orders of magnitude due to intrinsically and externally controllab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…It is readily shown that the second and third terms are complex conjugates of one another so there are just two integrals to compute in a numerical implementation. From (18) and the similar result for the expectation of C † 1 C 1 , we now have:…”
Section: Calculating the Probability For A Quantum Jumpsupporting
confidence: 56%
“…It is readily shown that the second and third terms are complex conjugates of one another so there are just two integrals to compute in a numerical implementation. From (18) and the similar result for the expectation of C † 1 C 1 , we now have:…”
Section: Calculating the Probability For A Quantum Jumpsupporting
confidence: 56%
“…Another setup for coherent feedback control consists of two 2LS interacting via the respective coupling gi with a single‐mode cavity . The cavity is pumped by a weak continuous‐wave pump field Ωgi and placed inside a semi‐infinite photonic waveguide which provides non‐Markovian feedback at delay time τ.…”
Section: Conventional Coherent Feedback Control Schemesmentioning
confidence: 99%
“…While a (destructive) feedback phase of ϕ=(2n+1)π, nN, (dot‐dashed lines) leads to low intensity and the suppression of antibunching, a (constructive) feedback phase ϕ=2πn, nN, (dotted lines) causes enhanced antibunching and high intensity. Adapted with permission . Copyright 2017, American Physical Society.…”
Section: Conventional Coherent Feedback Control Schemesmentioning
confidence: 99%
“…(2) and increasing reservoir-system entanglement spread. Possible strategies have been proposed in the Heisenberg picture [23], in the quantum cascaded approach based on Liouvillian [12] or on the quantum stochastic Schrödinger equation [11,27].…”
Section: Phenomenological Modelmentioning
confidence: 99%